SENSORY ANALYSIS AND OPTIMUM COOKING TIME DRY NOODLES WITH UNRIPE BERLIN BANANA FLOUR SUBSTITUTION - Ratih Putri Damayati; Ayu Febriyatna; Firda Agustin; Dina Fitriyah (Jurnal Gizi dan Pangan Soedirman, 2026)
Dry noodles are widely consumed and generally made from wheat flour, which is low in fiber and micronutrients. Substitution with unripe Berlin banana flour (UBF), rich in resistant starch, is expected to improve nutritional value while maintaining sensory and cooking quality. This study aimed to analyze the sensory characteristics, nutritional value, and optimal cooking time of dry noodles substituted with UBF. Sensory analysis was carried out using hedonic and hedonic quality tests of color, taste, aroma, texture, and stickiness with 36 semi-trained panelists. Three formulas were tested with UBF and wheat flour ratios of F1 (10:90), F2 (15:85), and F3 (20:80). The best formulation was determined using the effectiveness index, followed by a proximate analysis of the selected formulation. Optimal cooking time was assessed in triplicate, and statistical analysis was performed using one-way ANOVA. The results showed that all formulas were rated as neutral in sensory attributes, and the best formulation was F2 (20 g UBF: 80 g wheat flour) with an effectiveness index of 0.937. The best formulation contained 13.56% protein and 11.60% moisture content. This indicates that the dried noodles substituted with UBF comply with SNI. The optimal cooking time increased with higher levels of UBF substitution.